The Effectiveness of Psycho-Educational and Cognitive-Behavioral Counseling on Female Sexual Dysfunction - Firoozeh Mirzaee; Atefeh Ahmadi; Zahra Zangiabadi; Moghaddameh Mirzaee (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2020)
Abstract Introduction Sexual function is a multidimensional phenomenon that is affected by many biological and psychological factors. Cognitive-behavioral sex therapies are among themost common nonpharmacological approaches to psychosexual problems. The purpose of the present study was to investigate the effectiveness of psychoeducational and cognitive-behavioral counseling on female sexual dysfunction. Methods The present study was a clinical trial with intervention and control groups. The study population consisted of women referring to the general clinic of a governmental hospital in Iran. After completing the demographic questionnaire and Female Sexual Function Index (FSFI), those who obtained the cutoff score ≤ 28 were contacted and invited to participate in the study. Convenience sampling method was used and 35 subjects were randomly allocated for each group. Eight counseling sessions were held for the intervention group (two/week/1.5 hour). Post-test was taken from both groups after 1 month, and the results were statistically analyzed by PASW Statistics for Windows, Version 18 (SPSS Inc., Chicago, IL, USA). Results The total mean scores of FSFI and the subscales of sexual desire, arousal, orgasm, and satisfaction were significantly higher in the intervention group than in the control group after the intervention. In addition, postintervention pain mean scores in the intervention group were significantly lower than in the control group (p < 0.05). Conclusion The results of the present study indicate that psychoeducational cognitive- behavioral counseling is effective in improving female sexual function. It is recommended to compare the effects of psychoeducational cognitive-behavioral counseling on sexual dysfunctions of couples and with a larger sample size in future research.